2013
DOI: 10.1016/j.memsci.2012.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of thin film composite poly(amide)-carbon-nanotube supported membranes for enhanced performance in osmotically driven desalination systems

Abstract: Cite this article as: Ludovic Dumée, Judy Lee, Kallista Sears, Blaise Tardy, Mikel Duke and Stephen Gray, Fabrication of thin film composite poly(amide)-carbon-nanotube supported membranes for enhanced performance in osmotically driven desalination systems, Journal of Membrane Science, http://dx.doi.org/10. 1016/j.memsci.2012.09.026 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…Irregular shaped pores are changed to uniform size pores which allow water molecules easily pass through the membrane and thus high fluxes are obtained. We conclude that with the new pore shape arrangements, the pore structures also becomes align with each other, symmetrical throughout the membrane depth and thus resembles uniform structures close to the CNT membrane structures which have shown higher water flux [47,65]. It was observed that at there is a particular set of FS and DS flow rate which help get highest flux through the FO membrane.…”
Section: Effect Of Changing Ds and Fs Flow Ratementioning
confidence: 69%
See 1 more Smart Citation
“…Irregular shaped pores are changed to uniform size pores which allow water molecules easily pass through the membrane and thus high fluxes are obtained. We conclude that with the new pore shape arrangements, the pore structures also becomes align with each other, symmetrical throughout the membrane depth and thus resembles uniform structures close to the CNT membrane structures which have shown higher water flux [47,65]. It was observed that at there is a particular set of FS and DS flow rate which help get highest flux through the FO membrane.…”
Section: Effect Of Changing Ds and Fs Flow Ratementioning
confidence: 69%
“…Both these follow the same permeation rate and are readily rationalized by the filtration-type mechanism or a pore-flow membrane. PSF support layerusually showed pore sizes of 20-25 nm [65]. Due to the large pore size of membrane SL, it is suspected that the PSF support layer don't offer any molecular resistance to salt permeation and direct salt diffusion occur.…”
Section: Effect Of Changing Ds and Fs Flow Ratementioning
confidence: 99%
“…Tang et al have modeled a similar double-skinned FO membrane and have observed that the best double-skinned FO membrane should maintain a mass transfer coefficient that is high for the porous support, have a brackish water RO type draw skin, a feed skin with low rejection NF [142]. Su et al have also fabricated double-skinned CA hollow fibers consisting of an inner or outer selective layer by employing different phase inversion rates and extent of thermal annealing at Electro-spinning, phase separation and IP [135] 2012 TFC PA Super porous CNT non-woven Bucky-paper (BP) support, PA active layer Plasma treatment of CNT BPs support and IP [136] 2012 Dual layer hollow fiber NF PES inner support layer and PAI active layer post-treated by PEI Dry-jet wet spinning, one-step coextrusion, multi-layer polyelectrolyte depositions [137] 2013 Thin-film inorganic (TFI) Stainless steel mesh (SSM) substrate, micro-porous silica xerogels active layer Dip-coating and calcining for 4 h at 500°C in nitrogen followed by cooling to 25°C [118] 2014 Thin-film nanocomposite (TFN)…”
Section: Membrane Advancementmentioning
confidence: 99%
“…62 Also bucky papers made from Carbon Nanotubes (CNTs) and nanofiber mats formed from electrospun fibres have been suggested as good FO membrane support due to high porosity and tensile strength. 68,69 Structurally it has been argued that an open šfinger' like structure of the support is to be favoured over a more dense šsponge' like structure. 70 However a more open structure is also mechanically weaker and a more dense structure also may have a higher ICP.…”
Section: Remarksmentioning
confidence: 99%